British art cinema : creativity, experimentation and innovation - Newland, Paul (Lecturer in film studies); Hoyle, Brian, 1979- (Manchester University Press, 2019)
This is the first book to provide a direct and comprehensive account of British art cinema. Film history has tended to view British filmmakers as aesthetically conservative, but the truth is they have a long tradition of experiment and artistry, both within and beyond the mainstream. Beginning with the silent period and running up to the 2010s, the book draws attention to this tradition while acknowledging that art cinema in Britain is a complex and fluid concept that needs to be considered within broader concerns. It will be of particular interest to scholars and students of British cinema history, film genre, experimental filmmaking, and British cultural history.